RANCANG BANGUN SISTEM INFORMASI MONITORING SATUAN KERJA DALAM RANGKA GOOD GOVERNANCE - Muhammad Tajuddin; Abdul Manan (Universitas Bumigora, 2015)
Design of System Monitoring Unit in the framework of Good Governance Provincial Government of West Nusa Tenggara (NTB). The research is a survey research, namely by taking a sample of the population using questionnaires as a means of collecting. Research survey conducted for the purpose of explanation (explanatory or confrmatory) that provides an explanation of the relationship between variables through research and Examination formulated earlier. Methods in building these systems use System Development Life Cycle (SDLC) with structured techniques and engineering Prototyping with master data is divided into 5 form Stuffng the data, to 5 the form will each have a relationship, then the data is prioritized in advance in accordance with the following sequence: a .formulir workplace; b. Costs form; c. Data form barriers; d. Data form Projects Agency; e.formulir Barriers Project. This application is made does not mean that everything can be solved by good, so that what is desired by the government of NTB can be contained in this system. Constraints that occur are minor adjustments to the user desires with the rules that exist in programming and easiness in operationalising can be implemented as quickly as possible. The use of the control system must be properly addressed, either physical control, hardware control, device control, database control, and control brain ware, so that the system can be run in accordance with desired.